(untitled) (Global Journal of Human-Social Science, 2013)
Whether formal teaching of grammar is necessary or not for teaching a second/foreign language is a debatable issue now. The Communicative Language Teaching (CLT) which has been a buzz-word in the domain of language teaching pedagogies all over the world for the last few decades discourages overt grammar teaching. Like many other countries, in Bangladesh too, the Communicative Language Teaching (CLT) has been introduced for English language teaching. But with the introduction of CLT, the quality of English language teaching and learning has remarkably deteriorated in the country. As a result, it is now important to investigate the substantiality of the principles of CLT with respect to overt grammar teaching, may it be from the theoretical perspective or from the contextual perspective. Based on this investigation, it is also required to determine what should be the proper position of overt grammar teaching in English Language Teaching (ELT) in Bangladesh. The present article has attempted to address all these points.